2020
DOI: 10.1111/acer.14453
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol‐Impaired Myogenic Differentiation is Associated With Decreased Myoblast Glycolytic Function

Abstract: Background: Myopathy affects nearly half of individuals with alcohol use disorder (AUD), and impaired skeletal muscle regenerative potential is a probable contributing factor. Previous findings from our laboratory indicate that chronic in vivo and in vitro ethanol (EtOH) treatment decreases myogenic potential of skeletal muscle myoblasts. Myogenesis, a highly coordinated process, requires shifts in cellular metabolic state allowing for myoblasts to proliferate and differentiate into mature myotubes. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
(100 reference statements)
2
16
1
Order By: Relevance
“…4 A,B). Previously, significantly downregulated mRNA expression of hexokinase ( HK ), aldolase ( ALDO ), pyruvate kinase ( PK ) in myotubes versus myoblasts were reported 30 . Consistent results previously reported that glycolysis occurs in proliferating C2C12 myoblasts, which later is followed by a differentiation process accompanied by autophagy and mitophagy, resulting in increasing oxidative phosphorylation activity 31 , 32 .…”
Section: Resultsmentioning
confidence: 99%
“…4 A,B). Previously, significantly downregulated mRNA expression of hexokinase ( HK ), aldolase ( ALDO ), pyruvate kinase ( PK ) in myotubes versus myoblasts were reported 30 . Consistent results previously reported that glycolysis occurs in proliferating C2C12 myoblasts, which later is followed by a differentiation process accompanied by autophagy and mitophagy, resulting in increasing oxidative phosphorylation activity 31 , 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Naïve CD4 + T cells that were not activated and differentiated were plated (density of 2x10 6 /ml per well) in growth media without anti-CD3 and anti-CD28. Water pans containing 75 mM ethanol were changed daily to maintain the 50 mM ethanol concentration in the incubator atmosphere as previously described ( 26 ). Both 25 mM and 50 mM ethanol were used in preliminary studies, but 25 mM had no significant effect on CD4 + T cell differentiation (data not shown), hence all subsequent experiments were performed with 50 mM.…”
Section: Methodsmentioning
confidence: 99%
“…This impairment of glycolysis within the liver occurs, in part, due to an increase in the NADH/NAD + ratio, which depletes free NAD + cofactor availability for glycolytic enzymes, such as glyceraldehyde 3-phosphate dehydrogenase ( 25 ). Ethanol also decreases myoblast (muscle stem cells) glycolytic function and leads to decreased differentiation ( 26 ). Further, ethanol increases reactive oxygen species (ROS) formation in mitochondria, which can damage mitochondrial DNA and ETC proteins, leading to impaired mitochondrial function and cell death ( 24 , 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Parallel in vitro studies using naïve myoblasts exposed to 50 mM alcohol for 3 days show that direct alcohol exposure results in a contrasting shift in metabolic phenotype. This may be associated with the impaired myoblast differentiation as shown by the close correlation between ECAR and fusion index and the number of myotubes per field (Levitt et al, 2020).…”
Section: Alcohol‐associated Metabolic Dyshomeostasis: Potential Link ...mentioning
confidence: 99%